The relevance of placental location at 20–23 gestational weeks for prediction of placenta previa at delivery: evaluation of 8650 cases - Becker, R. H.; Vonk, R.; Mende, B. C.; Ragosch, V.; Entezami, M. (Ultrasound in obstetrics & gynecology, 2001)
Objective To determine the correlation between placental position at 20–23 weeks and incidence of birth complications caused by placental position. Subjects and methods In an ongoing prospective study, placental position was determined by transabdominal sonography as part of anomaly scanning at 20–23 gestational weeks, followed by transvaginal sonography in uncertain or suspicious situations. Examination was performed in 9532 cases; feedback was obtained from 8650 patients (90.7%). Results Transabdominal sonography was followed by transvaginal scan in 363 of 8650 cases (4.2%). In 8551 cases (98.9%), we found normal placental position, with the placenta not reaching the internal os and a Cesarean section rate of 17.1% (1458/8551). The incidence of ‘low placental position’, with the placenta reaching the internal os was 0.66% (57/8650), with a Cesarean section rate of 21% (12/57). In 0.49% (42/8650) of cases, the placenta overlapped the internal os at 20–23 weeks; Cesarean section because of placenta previa or bleeding was performed in 28 of 8650 cases (0.32%). Vaginal delivery was possible in 43% of cases (13/30), when the overlap did not exceed 25 mm. If the overlap exceeded 25 mm (12 cases), no vaginal delivery was reported. There was no reported case of placenta previa missed at the 20–23‐week scan. Conclusion At 20–23 weeks, a combination of routine transabdominal and indication‐based transvaginal location of placental position is a powerful tool in predicting placenta previa at delivery. The advantage of determining placental position at this stage of pregnancy is a low false‐positive rate compared to at earlier stages of pregnancy. We conclude that an overlapping placenta at 20–23 weeks has the consequence of a high probability of placenta previa at delivery. An overlap of 25 mm or more at 20–23 weeks seems to be incompatible with later vaginal delivery. Copyright © 2001 International Society of Ultrasound in Obstetrics and Gynecology